Meningkatkan Kemampuan Berbahasa Anak Usia 4-5 Tahun Melalui Metode Bercerita Denagn Bahan Alam Di Tk Bina Rahayu Kutai Karta Negara - Herni; Heppy Liana; Kartika Fajriani; Lailatul Hidayah; Yeni Aslina; Syahri Bulan (Manajemen Pendidikan Program Doktor, 2025)
Early childhood language skills are an important aspect in the development of communication and self-expression. However, in Bina Rahyu Kindergarten, Kutai Kartanegara, children aged 4-5 years show low language skills, such as difficulty speaking, stiffness when singing, and less responsive to social interactions. This research aims to improve children's language skills through storytelling methods using natural materials in the form of corn husks. This research is a Classroom Action Research (CAR) conducted in two cycles. The research subjects consisted of 8 children, namely 6 boys and 2 girls. Data collection techniques used observation, interviews, and documentation, with data analysis quantitatively and qualitatively descriptive percentages. Indicators of success include the ability to answer simple questions, express feelings and desires, mention natural materials from corn, and retell the content of the story. The results of the study showed that in the pre-cycle, the average achievement of language skills was 39%. In the first cycle it increased to 51%, the teacher's strategy of stimulating through a story entitled